Mix Method Study Of Acceleration Of Vaccination Acceptance In Community In Polewali And Campalagian Districts (Journal of Pharmaceutical Negative Results, 2023)
Objectives: This study examined the effectivity of subsystem components in community which could accept the acceleration of Covid-19 vaccine in Polman Region, therefore it becomes information for decision makers to create better health service management which is equal for everyone.Methods: this study applied mix method exploratory design which was conducted in two respective phases: qualitative and quantitative study. Qualitative study was conducted through focus group discussion on 3 target groups (primary, secondary and tertiary) to identify themes, ideas, perspectives, and believes, which became part of quantitative study to be explored. In quantitative study, 133 respondents were recruited from two boarding schools in the target area. Indepth interview and Focus group Discussion were used to collect data in the qualitative method. Quantitative study used descriptive statistics to describe information with frequency distribution.Results: The main results prove that there were relations between the variables found in the two methods which were significant and there was no internal conflict between the qualitative and quantitative findings. The result of the analysis found that the vaccine acceleration model which can be carried out namely involving local organizations and social groups in the COVID-19 information education system as well as taking preventive measures such as vaccination, and it will also be very effective if there were social relationships between individuals who were able to disseminate information about the importance of maintaining health protocols and also to conduct vaccinations in every level of society that could increase trust and follow-up for those who were still doubt about COVID-19 or about government's recommendation for vaccination.Conclusions: We conclude that each dimension of the social ecology and Health Belief Model was found to be consistent in both qualitative and quantitative research findings.